Upstream deregulation of calcium signaling in Parkinson’s disease - Rivero-Ríos, Pilar; Gómez-Suaga, Patricia; Fdez, Elena; Hilfiker, Sabine (Frontiers in Molecular Neuroscience, 2014)
Parkinson´s disease (PD) is a major health problem affecting millions of people worldwide. Recent studies provide compelling evidence that altered Ca2+ homeostasis may underlie disease pathomechanism and be an inherent feature of all vulnerable neurons. The downstream effects of altered Ca2+ handling in the distinct subcellular organelles for proper cellular function are beginning to be elucidated. Here, we summarize the evidence that vulnerable neurons may be exposed to homeostatic Ca2+ stress which may determine their selective vulnerability, and suggest how abnormal Ca2+ handling in the distinct intracellular compartments may compromise neuronal health in the context of aging, environmental and genetic stress. Gaining a better understanding of the varied effects of Ca2+ dyshomeostasis may allow novel combinatorial therapeutic strategies to slow PD progression.